Visualizing and understanding l'hopital's rule‡. Issue 7 (3rd October 2017) - Gordon, Sheldon P.
ABSTRACT: This article uses dynamic software in Excel to demonstrate several ways in which graphical and numerical approaches can be introduced both to enhance student understanding of l'Hopital's Rule and to explain why the Rule actually works to give the 'right' answers. One of the approaches used is to visualize what is happening by examining the limits with both l'Hopital's Rule and the associated Taylor approximation to the function. The dynamic software allows students to experiment with the ideas.